LTspice implementation of PKU compact model of metal-oxide-based RRAM: part C_simulation of RRAM memory arrays - Du, Yifan (Nanyang Technological University, 2022)
RRAM, which has the characteristics of high speed, low power consumption, easy integration, compatibility with CMOS technology, is a potential NVM technology. It is considered as the next-generation high density storage and high-performance computing technology, and also, a powerful alternative of flash memory technology.